Nature of the Communications Phenomenal. Case Study: Narrative of Life History of Dr. Marija Sereikienė-Kiškytė (B. 1925) in the Book of Memories “Mano Laikas” (My Time) - Pečeliūnaitė, Angelė (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English] The article analyzes the nature of phenomenal communication. The phenomenal communication is exceptional abilities to socialize and to communicate information. A person having a phenomenal communication, attracts attention surrounding, tend to be a leader, looking for and finding a solution that fits the situation. The article is performed personal narrative analysis, refer on the constructivist theory methodology. The Phenomenal communication genesis is analyses too. It was found that the nature of phenomenal communication is closely associated with strong genealogical family ties, with the early perceived social status and giving an significance social relations, with the ability to make independent decisions and with altruistic activities. It should be noted that the quality of communication is such an important activity, as interest in his fellow countrymen and their destinies, constant self-education, social activities, education attainment, the dialogue between different generations support. It was found that the genesis of phenomenal communication is closely linked with strong emotionally lived events. The phenomenal communication leads to personal satisfaction in the intellectual, emotional, moral and spiritual existence. Generally we can said that phenomenal communication is characterized by educated, intelligent, independent personality, which is characterized by “an open mind”, aims to constantly be in the midst of events, hold the contacts with people of different generations, have plans for the future. Likely, that the phenomenal communication could be one of the subjective factor of the quality of life.